Antarctica in the Australian Imagination - Elizabeth Leane; Pfennigwerth, SC (2002)
Antarctica and Australia share a geographical marginality, a commonality that has produced and continues to reinforce historical and political ties between the two continents. Given this close relationship, surprisingly few full-length novels set in or concerned with the Antarctic have been produced by Australian authors. Until 1990, two late-nineteenth-century utopias, and two novels by Thomas Keneally, were (to our knowledge) the sole representatives of this category. The last decade, however, has seen an upsurge of interest in Antarctica, and a corresponding increase in fictional response. Keneally's novels are 'literary,' but these more recent novels cover the gamut of popular genres: science fiction, action-thriller, and romance. Furthermore, they indicate a change iÅ„ the perception of Antarctica and its place within international relations. Whereas Keneally is primarily concerned with the psychology of the explorer from the 'Heroic Age,' these younger Australian writers are interested in contemporary political, social, and environmental issues surrounding the continent. Literary critics have hitherto said little about textual representations of Antarctica; this paper opens a space for analysis of 'Antarctic fiction,' and explores the changing nature of Australian-Antarctic relations as represented by Australian writers.